The Characteristics Of Banyumas People As Seen In Leng-ger Banyumasan Lyrics (Ethnolinguistics Approach) - Wilda Putri Festiyanti (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
This research was conducted in order to find out the characteristics of Banyumas people via the lyrics of Lengger Banyumasan, as one of the work arts, that the lyrics reflect the culture and also the society's thought. The researcher tries to focus the research only in the one of districts in Banyumas region named Ajibarang as this district is a very special place that in the past time it was a region (on the colonialism era). The researcher thinks that it is a phenomenon in the field of ethnolinguistics, which can enrich the language people knowledge about how language depicts the culture of society in certain place that can be also their identity, which differ them from any other society at the same region. In order to collect the data, the researcher uses direct observation among the society of Ajibarang about the lyrics of Lengger Banyumasan. The researcher records and writes the data by doing a direct interview in order to get the data the researcher needed. After the researcher has collected the data, it was founded that the 11 famous songs of Lengger Banyumasan show different characteristics of the people in Ajibarang. So it can be concluded that they have various way to express their idea including via the Ivrics of song, or it can be said that song is the way to express one-way communication of social criticisms.